Targeting Cholesterol Homeostasis to Fight Hearing Loss: A New Perspective - Malgrange, Brigitte; Varela-Nieto, Isabel; de Medina, Philippe; Paillasse, Michael R. (Frontiers in Aging Neuroscience, 2015)
Sensorineural hearing loss (SNHL) is a major pathology of the inner ear that affects nearly 600 million people worldwide. Despite intensive researches, this major health problem remains without satisfactory solutions. The pathophysiological mechanisms involved in SNHL include oxidative stress, excitotoxicity, inflammation and ischemia resulting in synaptic loss, axonal degeneration and apoptosis of spinal ganglion neurons. The mechanisms associated with SNHL are shared with other neurodegenerative disorders. Cholesterol homeostasis is central to numerous pathologies including neurodegenerative diseases and cholesterol regulates major processes involved in neurons survival and function. The role of cholesterol homeostasis in the physiopathology of inner ear is largely unexplored. In this review, we discuss the findings concerning cholesterol homeostasis in neurodegenerative diseases and whether it should be translated into potential therapeutic strategies for the treatment of SNHL.